Pie - Weeks, Sarah 1955- (Scholastic Press, 2011)
After the death of Polly Portman, whose award-winning pies put the town of Ipswitch, Pennsylvania, on the map in the 1950s, her devoted niece Alice and Alice's friend Charlie investigate who is going to extremes to find Aunt Polly's secret pie crust recipe. Includes fourteen pie recipes.